RELATIONSHIP OF TEACHER COMMUNICATION TO STUDENT LEARNING MOTIVATION OF FIFTH GRADE IN ELEMENTARY SCHOOL TANGERANG 6 TANGERANG CITY - Mawardi, Mawardi (DIDAKTIKA TAUHIDI: JURNAL PENDIDIKAN GURU SEKOLAH DASAR, 2018)
Mawardi, Nesti Riksayanti. "Relationship of Teacher Communication to Student Learning Motivation of Fifth Grade In Elementary School Tangerang 6 Tangerang City". University of Muhammadiyah Tangerang 2017. This research to purpose communication of teacher with student so that hamper learning process and students learning motivation. to achieve the interaction of teaching and learning needs a clear communication, so that students can be successful in learning tasks and achieve the expected learning objectives. This research was conducted to find out (1) teacher communication (2) learning motivation (3) teacher communication relation to student learning motivation of fifth grade in Elementary School Tangerang 6. This research uses quantitative research type with survey method, while the technique used is observation, interview, documentation and spreading of questionnaire. The total population is 95 students in fifth grade Elementary School Tangerang 6 with sampling technique using random sampling. The research instrument used is the questionnaire which has been tested the validity level of 75 students. Instrument data collection for teacher communication (variable X) and student learning motivation (variable Y) using questionnaire Likert scale with 5 choices of answers that is always, often, sometimes, almost never, never. Hypothesis testing is done by using the Product Moment correlation formula, which begins with the normality test of the data obtained. Based on the result of research known there is a significant positive correlation between teacher communication (X) to student learning motivation (Y). This is evidenced by the Product Moment correlation test that produces of 0.840 is at the interval of 0.80 to 1.00 which means it has a very strong correlation. And for the hypothesis obtained data for tcount = 13.242 while ttable 0.05 = 1.993. This shows that the value of tcount> ttable which means research hypothesis (H1) accepted. From the results of this study, it can be concluded that there is influence between teacher communication to student learning motivation in Elementary School Tangerang 6. And also expected bias to provide information and input for teachers and students that communication in education is very important and good effect on student learning motivation.